Tantangan hukum dalam pengembangan usaha mikro, kecil, dan menengah (UMKM) di Kota Jambi: perspektif perlindungan hukum bagi pelaku UMKM - Nugraha, Muhammad Valiant Arsi; Dwi Arita Deli, Mutia; Eriton, Muhammad; Rizki Ruswandi, Melia (Proceedings Academic Universitas Jambi, 2025)
This research explores the legal obstacles encountered by Micro, Small, and Medium Enterprises (MSMEs) in Jambi City, focusing on issues of legal protection and the effectiveness of regulatory implementation. Adopting a socio-legal methodology within a qualitative framework, the study gathered data through literature analysis, in-depth interviews, and direct field observations involving MSME practitioners. The results indicate that most MSMEs face considerable difficulties concerning business formalization, brand registration, licensing procedures, and insufficient awareness of their legal entitlements. Although several laws, including Law No. 20 of 2008 on MSMEs and the Job Creation Law, provide a legal foundation, their enforcement at the municipal level remains limited. The originality of this study lies in its empirical assessment at the local level, highlighting the discrepancy between normative legal provisions and real-world practices. The findings suggest that adaptive reforms, simplified administrative licensing systems, and accessible legal aid services are pivotal to enhancing MSME resilience and competitiveness. From a theoretical standpoint, the study enriches the discourse on MSME legal governance, while in practical terms, it offers strategic policy insights for local authorities to improve legal certainty, access to justice, and sustainable business development.